Scanning mutagenesis of the arginine-rich region of the human immunodeficiency virus type 1 Rev trans activator. - Hammerschmid, M (1994)
The structural proteins of human immunodeficiency virus type 1, for example, Gag and Env, are encoded by unspliced and incompletely spliced viral transcripts. The expression of these mRNAs in the cytoplasm, along with their commensurate translation, is absolutely dependent on the virally encoded Rev trans activator. Previous studies have demonstrated that Rev binds directly to its substrate mRNAs via an arginine-rich element that also serves as its nuclear localization sequence. In an attempt to define the specific amino acid residues that are important for in vivo activity, we have constructed a series of missense mutations that scan across this region. Our data demonstrate that all eight arginine residues within this element can, individually, be substituted for either leucine or lysine with no apparent loss of function. Importantly, these findings suggest that no single amino acid within the arginine-rich domain of Rev is, by itself, essential for activity and that considerable functional redundancy is therefore likely to exist within this region. Interestingly, one mutant in which a tryptophan had been substituted for a serine failed to accumulate exclusively in the nucleus but still bound RNA in a manner that was indistinguishable from that of the wild-type protein. This observation indicates that features of the arginine-rich region that are additional to those required for RNA binding are important for Rev's correct accumulation in the nucleus.